Gut microbiota in autism and mood disorders - Mangiola, Francesca (World J Gastroenterol, 2016)
The hypothesis of an important role of gut microbiota in the maintenance of physiological state into the gastrointestinal (GI) system is supported by several studies that have shown a qualitative and quantitative alteration of the intestinal flora in a number of gastrointestinal and extra-gastrointestinal diseases. In the last few years, the importance of gut microbiota impairment in the etiopathogenesis of pathology such as autism, dementia and mood disorder, has been raised. The evidence of the inflammatory state alteration, highlighted in disorders such as schizophrenia, major depressive disorder and bipolar disorder, strongly recalls the microbiota alteration, highly suggesting an important role of the alteration of GI system also in neuropsychiatric disorders. Up to now, available evidences display that the impairment of gut microbiota plays a key role in the development of autism and mood disorders. The application of therapeutic modulators of gut microbiota to autism and mood disorders has been experienced only in experimental settings to date, with few but promising results. A deeper assessment of the role of gut microbiota in the development of autism spectrum disorder (ASD), as well as the advancement of the therapeutic armamentarium for the modulation of gut microbiota is warranted for a better management of ASD and mood disorders.